Influence of Consumer Motivation, Perception of Quality, and Consumer Attitudes toward Outdoor Equipment Purchase Decisions - Padmantyo, Sri; Diwirsyah, Andrivan (Prosiding University Research Colloquium, 2023)
is study aims to analyze the influence of consumer motivation, quality perception and consumer attitudes towards outdoor equipment purchase decisions. This is a quantitative research. The sampling technique used is non-probability sampling with a sample of 194 people. The data collection technique uses questionnaires from the google form platform which are distributed through whatsapp groups online. The results indicate that consumer motivation, quality perception and consumer attitude have a significant positive effect on purchasing decisions outdoor equipment. Simultaneously the three independent variables affect the dependent variable.